Supervisi Klinis Sebagai Upaya Peningkatan Kemampuan Guru Memahami Bahan Ajar di Sekolah - Swirna DJ. Kau; Imran Atute (Jurnal Didaktika Pendidikan Dasar, 2023)
Teaching materials are something that is meaningful to students and teachers. This study aims to improve the teacher's understanding ability about teaching materials using clinical supervision of teachers at SMP Negeri 2 Satap Tabongo. This study uses a quantitative method with data collection techniques namely observation and documentation, with data analysis techniques that describe in detail the planning, implementation and observation. The results of this study indicate that clinical supervision can improve the ability of SMP Negeri 2 Satap Tabongo teachers to understand teaching materials. This can be seen from the 5 indicators of mastery of teaching materials, namely the ability to (a) plan teaching materials, (b) organize teaching materials, (c) choose teaching materials according to the needs and characteristics of students, (d) collaborate teaching materials with other learning sources , and (e) using teaching materials in the learning process.